... if you sailed on the Mayflower. - McGovern, Ann.; Handlesman, J. B. (New York, Scholastic Inc., 1969)
Questions and answers describe the voyage of the Mayflower and the Pilgrim's first year in the New World.
Keywords: Mayflower (Ship) -- Juvenile literature; Mayflower (Ship); Pilgrims (New Plymouth Colony) -- Juvenile literature; Pilgrims (New Plymouth Colony)